The Neuroethology of Rhythmic Communication : Neural and Mechanical Building Blocks and Constraints on Rhythm Production and Perception - Sauciuc, Gabriela-Alina; Schneider, Jennifer; Hattori, Yuko (Nature Beats: the What, Why and How of Animal Rhythmic Behaviours, Sweden, 2022-05-10 - 2022-05-12, 2025)
Humans and animals communicate with rhythmic behaviours that vary greatly in terms of temporal parameters and patterns. In this chapter we discuss the neuromuscular architecture underlying rhythmic behaviours and address factors that constrain their rhythmic properties. In Part I of the chapter we provide background regarding the building blocks of rhythmic communication from the muscles to the brain and then illustrate how these building blocks are coordinated within a single system (e.g. locomotor appendage apparatus, vocal articulatory apparatus, etc.) and across relevant systems (locomotor, respiratory and vocal). In Part II we illustrate how variations in anatomical design and physiological function constrain rhythmic production, in particular properties such as frequency rate, stability, versatility and pattern complexity. We also provide examples of putative mechanisms that influence rhythm perception across species. By reviewing and discussing these aspects of the neuroethology of rhythmic communication, we hope to infuse current mechanistic theorising on the evolution of rhythmic competence(s) with novel insights from research that, historically, has had less weight in this area of study. We also hope that the design of future experimental studies aimed at testing evolutionary hypotheses will benefit from increased awareness of how variations in aspects of muscular and vocal tract design, along with ‘low-level’ neural mechanisms shape rhythmic communication.